The Model of Bahasa Indonesia Teaching Materials Taken from Stories in Quran Taught with Content and Language Integrated Learning Approach - Izzah, Izzah; Rafli, Zainal; Ridwan, Sakura (Universitas Negeri Semarang, 2018)
This research aims to develop model of Bahasa Indonesia teaching materials which are taken from stories in Quran by using Content and Language Integrated Learning (CLIL)approach in grade 7 of Madrasah Tsanawiyah Muqimus Sunnah Palembang. Research method employed in this study is Research and Development (R&D). The research procedure undertaken in this study is taken from theory of Borg and Gall that consists of three steps, i.e. introduction, development, and evaluation. Meanwhile, for the data collection technique, this study implements documentation, observation, questionnaire, interview, and test. As for the validity and reliability of the model of teaching materials in this study, researchers ask for assessment and evaluation from experts, i.e. the syllabus expert, Bahasa Indonesia expert, and Islamic religion expert. The result shows that the teaching material model is effective and eligible to be used. The highest score of the experimental class is 95 and the lowest score is 74, while the average score is 87. Meanwhile, the highest and lowest score of the control class are 84 and 64, respectively, with average score of 77.5. Moreover, the average score between the experimental and control group also has been tested and counted by using t-test and shows a significant result, that ist = 1.685.